Comparative Analysis of Green Building Hospitals in Karawang and Pemalang - Pontan, Darmawan; Irawan, Angga Ananda; Fawwaz, Arvyant Arrazaqi; Abidin, Dikky Safitra; Hevada T, Laska; Sumeru, Indrawati (Journal La Multiapp, 2024)
This study aims to analyze and compare the application of the green building concept in two hospitals in Indonesia, namely Permata Keluarga Karawang Hospital and Dr. M. Ashari Pemalang Regional General Hospital (RSUD). Using descriptive qualitative methods and case study approaches, data were collected through observation, interviews, documentation, and measurements in the field. The results show that both hospitals have applied green building principles in various aspects such as energy efficiency, environmental management, and B3 waste management. Permata Keluarga Karawang Hospital excels in the use of energy-saving technology and waste management, while Dr. M. Ashari Pemalang Hospital stands out in staff involvement and environmental management. However, there are still several aspects that need to be improved by both hospitals, such as bicycle parking facilities and rainwater intake systems, to achieve more optimal green building standards. In conclusion, both hospitals have shown a strong commitment to environmental sustainability through the implementation of the green building concept, but further improvements are still needed to achieve more optimal results.